CTX-M-1 and CTX-M-15-producing Escherichia coli in dog faeces from public gardens. Issue 1 (December 2015) - Damborg, Peter; Morsing, Malene; Petersen, Tanja; Bortolaia, Valeria; Guardabassi, Luca
Abstract Background Extended-spectrum beta-lactamase (ESBL)-producingEscherichia coli are increasingly reported in dogs. The objective of this study was to provide data on the prevalence of ESBL-producingE. coli in dog faecal deposits in public gardens. Results A total of 209 faecal deposits collected in nine public gardens in Copenhagen, Denmark were screened by selective enrichment followed by plating on MacConkey agar supplemented with cefotaxime. Presumptive ESBL-producingE. coli were confirmed by MALDI-TOF MS and polymerase chain reaction (PCR) for detection of common cefotaxime resistance determinants (bla TEM, bla SHV, bla CTX-M andbla CMY-2 ). ESBL-producers were further characterized by multilocus sequence typing (MLST) and antimicrobial susceptibility testing using broth microdilution. Plasmids harbouring ESBL genes were characterized by S1 nuclease pulsed field gel electrophoresis, PCR-based replicon typing, and pMLST. Cefotaxime-resistantE. coli were detected in four (1.9 %) samples. Three samples harboured CTX-M-1-producing isolates, and one sample contained two CTX-M-15-producing isolates displaying distinct colony morphology. All isolates belonged to distinct sequence types (STs), including oneE. coli lineage previously associated to a human-specific pathotype (ST59).bla CTX-M-1 was carried on IncI1 plasmids classified as ST3 or ST58 by pMLST, whereasbla CTX-M-15 was located on IncF/Y and non-typeable plasmids in the two strains isolated from the same sample. Conclusions The study shows that dog faeces are a vector for dissemination of CTX-M-producingE. coli within urban areas. The risk derived from human exposure to dog faeces in public gardens depends on the prevalence of these bacteria in the local dog population as well as on the owners' practice to remove and dispose their dog's faeces.